Potential health benefits of blueberry and raspberry pomace as functional food ingredients: Dietetic intervention study on healthy women volunteers - Popović, Tamara; Šarić, Bojana; Martačić, Jasmina Debeljak; Arsić, Aleksandra; Jovanov, Pavle; Stokić, Edita; Mišan, Aleksandra; Mandić, Anamarija (Frontiers in Nutrition, 2022)
The fruit juice industry generates pomace as a valuable by-product especially rich in polyphenols, dietary fibres, vitamins, minerals, and unsaturated fatty acids. In the cookies used in this study, 30% of the gluten-free flour was replaced with dried and ground blueberry and raspberry pomace, rich source of polyphenols, dietary fibres, linoleic and alpha-linolenic acid. In order to examine whether the addition of blueberry and raspberry pomace in cookie formulation can have beneficial effects on certain blood parameters and anthropometric measurements, the designed cookies were tested in 20 healthy, normally fed female subjects, aged 30-50 years (41.35 ± 8.58 years) over four-week dietetic intervention study. Significant changes in the composition of fatty acids serum phospholipids, decrease in LDL-cholesterol level (20.16%), increase in adiponectin level (25.52%) and decrease in ALT and AST values were observed, thus indicating that inclusion of cookies containing blueberry and raspberry dried and ground pomace to usual diet might have positive effects on certain cardiovascular risk factors and liver function indicators.